PENGARUH IQ, KEPEMILIKAN LITERATUR IPS TERPADU DAN BUDAYA MEMBACA SISWA TERHADAP HASIL BELAJAR IPS TERPADU - Bagus Rusdianto; Yon Rizal; Darwin Bangun (JEE (Jurnal Edukasi Ekobis), 2013)
This study aimed to determine whether there is an influence (IQ) of students, student ownership of Integrated IPS literature, and culture of reading students' learning outcomes IPS Integrated semester eighth grade students of SMP Negeri 24 Bandar Lampung in the school year 2012/2013.The population in this study were all eighth grade students of SMP Negeri 24 Bandar Lampung in the academic year 2012/2013, amounting to 232 students with a sample of 147 students. The method used in this research is descriptive method verification with ex post facto approach and survey.      1.            There is the influence of intelligence quotient (IQ) on learning outcomes IPS Integrated Odd Semester Grade VIII Junior High School 24 Bandar Lampung.      2.            There is the influence of the ownership literature Integrated IPS IPS students' learning outcomes Integrated Odd Semester Grade VIII Junior High School 24 Bandar Lampung.      3.            There are cultural influences on learning outcomes of students' reading IPS Integrated Odd Semester Grade VIII Junior High School 24 Bandar Lampung.      4.            There is the influence of intelligence quotient (IQ), Integrated IPS student ownership literature, and culture of reading in students' learning outcomes IPS Integrated semester eighth grade students of SMP Negeri 24 Bandar Lampung.